Pendidikan Tinggi Islam dan Tantangan Dunia Kerja pada Era Digital - Jamil, Awaludin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
Based on PD Dikti, as of December 2024, the number of Religious Universities is 1,565 units. Meanwhile, according to the Emis data of the Director General of Pendis, the total Islamic Higher Education (PTKI) is 847 institutions, with details of 788 Private Islamic Higher Education (PTKIS) and 59 State Islamic Higher Education (PTKIN). his article discusses the challenges of the world of work for PTKI in the digital era and provides alternative solutions to these challenges. This article uses a qualitative approach and library research–data collection techniques through documentation of data sources in the form of relevant literature. Then analyzed with an interactive model to produce the following article findings: First, there are five challenges of the world of work in the digital era for PTKI: a) Digital literacy; b) Hard skills; c) Soft skills; d) Artificial Intelligence (AI); e) Gig economy. Second, alternative solutions to the challenges of the world of work in the digital era for PTKI are: a) Integration of digital literacy in the tridharma of higher education, such as lectures based on the Learning Management System (LMS), research based on the Open Journal System (OJS) and community service based on digital training; b) Implementation of the Outcome Based Education (OBE) Curriculum which is oriented towards the dynamic-contextual needs of graduates; c) Fulfilling the Competency Standards for PTKI Graduates, based on the Decree of the Director General of Islamic Education Number 102 of 2019 concerning Religious Standards for Islamic Higher Education which includes attitudinal, intellectual and skill competencies; d) Education on the Use of AI by adopting the Guidebook for the Use of Generative Artificial Intelligence (GenAI) in Higher Education Learning Published by the Ministry of Education, Culture, Research and Technology in 2024; e) Collaboration between PTKI and DUDI (Industrial World Business World) to overcome deskilling and skill traps through the Merdeka Learning Campus Merdeka (MBKM) program such as certified internships. The limitations of this article are theoretical. Suggestions for further studies are quantitative research at PTKIN and/or PTKIS.